DEVELOPMENT OF E-MODULE WITH PROBLEM-BASED LEARNING MODEL ON HUMAN DIGESTIVE SYSTEM MATERIALS AT SMPN CITY OF BENGKULU - Sri Widia Astuti; Sukarno Sukarno; Meirita Sari (EDUPROXIMA : Jurnal Ilmiah Pendidikan IPA, 2024)
This research is a type of ADDIE model development research aimed at developing e-modules based on problem-based learning models. The percentage of achievement of the feasibility analysis results is 80.6% for material experts, 97.3% for linguists, and 95% for media/design experts that the product is suitable for use. The response results showed "very practical" criteria with an average percentage of students in the initial trial of 87.6%, operational trial students of 87.34%, and science education teachers of 90%. The calculation of the paired sample t-test with a significance level of 0.05 and degrees of freedom (df) = 29 obtained a sig value. (2-tailed) 0.000 0.05 and tcount = 20.239 and ttable = 2.045, the average pretest score was 48.6 and the posttest showed a higher average score of 86.5 which resulted in very “effective criteria”.  The null hypothesis (H0) is rejected and (Ha) is accepted because tcount is greater than ttable. This means that students who use e-modules get better learning outcomes. The findings of this study indicate that the e-module created has been successfully used as a student learning resource on human digestive system material to support the teaching and learning process at SMP Negeri Kota Bengkulu.